DETERMINAN EFEKTIVITAS SISTEM KEUANGAN DESA (SISKEUDES) DI KECAMATAN KARANG BARU - Rizkina; Afrah Junita; Agustina Nurul Fajriah (Jurnal Mahasiswa Akuntansi Samudra, 2025)
This study aims to determine the effect of superior support, user participation, and education level on the effectiveness of the use of the village financial system (SISKEUDES) in Karang Baru District. This study applies a quantitative method by utilizing primary data collected using a questionnaire. The population of this study includes all village officials in 31 villages located in Karang Baru District. The total sample of 93 respondents was selected through a saturated sampling method. This study applies analytical methods including descriptive statistics, multiple linear regression, data quality testing, classical assumption testing, and hypothesis testing. Data processing was carried out using SPSS version 25 software. Based on the analysis findings, it was found that superior support, user participation, and education level have an influence on the effectiveness of the use of the Village Financial System (SISKEUDES). For further research, it is recommended to include additional independent variables to identify more factors that can influence the effectiveness of the village financial